Penguatan Kompetensi Manajerial Guru Melalui Pelatihan Penyusunan Perangkat Pembelajaran dengan Pendekatan Deep Learning di SMK Muhammadiyah 2 Tangerang Selatan - Maulana Iman Jaya; Nurrabiatul Nurrabiatul; Muhammad Hambali; Nida Aulia Nurfadillah; Sederhana Zai; Saiful Anwar; Yulita Pujilestari; R. Dede Siswandi (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
Teachers’ managerial competence plays a crucial role in ensuring effective and relevant learning, particularly in vocational education. Teachers are required not only to master subject matter but also to plan, manage, and evaluate learning through well-structured and contextual learning tools. This Community Service activity aimed to strengthen teachers’ managerial competence through training on the development of learning tools using a deep learning approach at SMK Muhammadiyah 2 Tangerang Selatan. The implementation method included conceptual material delivery, practical training, and mentoring in designing learning tools. The deep learning approach was applied to encourage learning designs that emphasize deep understanding, critical and reflective thinking, and alignment with workplace demands. The results showed an improvement in teachers’ understanding and skills in developing more systematic, innovative, and adaptive learning tools aligned with 21st-century competencies. This activity contributed positively to strengthening teachers’ roles as learning managers and supporting the improvement of learning quality in vocational schools.